Oxidative stress and antioxidant responses in Nile tilapia Oreochromis niloticus experimentally infected by Providencia rettgeri - De Freitas Souza C. (2019)
© 2019 Elsevier Ltd Bacterial diseases are one of the major problems in freshwater fish culture and have been linked to significant losses and high mortality rate. In this study, Nile tilapia Oreochromis niloticus was infected by Providencia rettgeri to evaluate the oxidative stress and antioxidant responses in the fish tissues. Juvenile Nile tilapia was divided into two groups, as follow: control (uninfected) and experimentally infected with 100 μL of P. rettgeri suspension containing 2.4 × 10 7 viable cells/fish, and the liver and kidney tissues were collected on days 7 and 14 post-infection (PI). Liver and kidney ROS and lipid peroxidation levels were high in infected fish on day 14 PI compared to control group, while superoxide dismutase activity was lower in liver (days 7 and 14 PI) and kidney (day 14 PI) compared to their respective control groups. Liver and kidney antioxidant capacity against peroxyl radicals, non-proteic, and proteic thiols levels was lower in infected tilapia on day 14 PI compared to control group. Based on these results, P. rettgeri infection may elicit oxidative damage via increased ROS production, decreased ROS elimination and inhibits enzymatic and non-enzymatic antioxidant defense systems; which may contribute directly to disease pathophysiology of infected animals.